2018
DOI: 10.1159/000489948
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Metastatic Brain Tumors from Malignant Melanomas: A Japanese Multi-Institutional Cooperative and Retrospective Cohort Study (JLGK1501)

Abstract: Background: The incidences of metastatic brain tumors from malignant melanomas have increased and survival has been prolonged by novel molecular targeted agents and immunotherapy. However, malignant melanomas are uncommon in Asian populations. Objectives: We retrospectively analyzed treatment efficacy and identified prognostic factors impacting tumor control and survival in Japanese melanoma patients with brain metastases treated with gamma knife radiosurgery (GKRS). Methods: We retrospectively reviewed the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The generalization of SRS may have improved the median OS. The effectiveness of SRS has also been reported in other malignancies, such as renal cell carcinoma 38 and malignant melanoma 39 . Regarding sarcomas, SRS was performed in 5.9%–15% of patients with BM 2,3,7,10 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The generalization of SRS may have improved the median OS. The effectiveness of SRS has also been reported in other malignancies, such as renal cell carcinoma 38 and malignant melanoma 39 . Regarding sarcomas, SRS was performed in 5.9%–15% of patients with BM 2,3,7,10 .…”
Section: Discussionmentioning
confidence: 84%
“…The effectiveness of SRS has also been reported in other malignancies, such as renal cell carcinoma 38 and malignant melanoma. 39 Regarding sarcomas, SRS was performed in 5.9%–15% of patients with BM. 2 , 3 , 7 , 10 In our study, SRS was performed in 25% of patients, showing a higher frequency than in previous reports, and was significantly correlated with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of Asian patients with MBMs showed a median OS of 7-8 months, which is comparable to our findings. 11,12 Although previous studies have shown limited effectiveness of ICI and TT in Asian patients with unresectable melanoma, Asian patients with MBMs may also respond poorly to these systemic therapies. 8 The associated factors identified in multivariate analysis were primary location, serum LDH levels, type of initial systemic therapy, and type of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that patients treated with STI had longer survival than those treated with WBRT. Previous studies have demonstrated the effectiveness of STI over WBRT 11 . In general, STIs are preferred for up to four brain metastases 26 .…”
Section: Discussionmentioning
confidence: 99%
“…9 While the local control rate of multi-agent ICI is encouraging, it is important to remem-ber that the 57% rate remains vastly inferior to the six-month local control rates of 87-91% achieved following single-fraction SRS administered via linear accelerator or Gamma Knife. 6,[10][11][12] Candidates for SRS are typically patients with 1-10 brain metastases, while patients exceeding 10 brain metastases often receive WBRT instead of SRS. 13 1.3.…”
Section: Treatment Of Brain Metastasesmentioning
confidence: 99%